KONSEP TEORI PROGRAM PENGEMBANGAN PERENCANAAN PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Syakirin; Purniadi Putra; Mashudi (PIJAR: Jurnal Pendidikan dan Pengajaran, 2022)
The purpose of this study is to describe and analyze programs in the development of Islamic Religious Education in making learning plans in schools. This research method uses qualitative research with a liberal research type. As for collecting data using books, journal articles, and websites that are relevant to the research title. The results of the research are the formation of a system as an overall strategy or plan composed by a set of harmonious elements, presenting a unitary unit, each element and the existence of a logical and analytical approach to various fields. By identifying the objectives, the components contained in the system can be analyzed. The philosophical core idea is that a system is a collection of a number of components, which interact and are interdependent on one another.